Impact of air pollution on healthcare utilization in patients with bronchiectasis - Hyun Lee; Sang Hyuk Kim; Sun-Kyung Lee; Sun-Kyung Lee; Hayoung Choi; Sung Jun Chung; Dong Won Park; Tai Sun Park; Ji-Yong Moon; Tae-Hyung Kim; Sang-Heon Kim; Jang Won Sohn; et al. (Frontiers in Medicine, 2023)
IntroductionAir pollutants are increasingly recognized to affect long-term outcomes in patients with bronchiectasis. We aimed to figure out the association between air pollutants and the risk of healthcare utilization in patients with bronchiectasis.MethodsData for 1,029 subjects with bronchiectasis in Seoul were extracted. The air pollutants included particulate matter of 10 μm or less in diameter (PM10), particulate matter of 2.5 μm or less in diameter (PM2.5), sulfur dioxide (SO2), carbon monoxide (CO), ozone (O3), and nitrogen dioxide (NO2). The outcome was all-cause healthcare uses, defined as outpatient visit, emergency department visit, or hospitalization. The concentration–response curves between each air pollutant and relative risks for healthcare utilization were obtained.ResultsThere were significant correlations between air pollutant concentrations and the risk of healthcare utilization, particularly for PM10, NO2, SO2, and CO. This risk was observed even at concentrations below the recommended safe thresholds for the general population. The slopes for the association between PM10 and NO2 and the risk of healthcare use showed a logarithmic growth pattern, with the steepest increase up to 30 μg/m3 and 0.030 parts per million (ppm), respectively. The curves for SO2 and CO showed an inverted U-shaped pattern, with a peak at 0.0045 ppm and a slow upward curve, respectively. No specific trends were observed for PM2.5 and O3 and the risk of healthcare use.DiscussionIncreased concentrations of PM10, NO2, SO2, and CO were associated with increased healthcare utilization in patients with bronchiectasis. For patients with bronchiectasis, there were no safety thresholds for those air pollutants, and even low levels of air pollutant exposure can negatively impact bronchiectasis outcomes.